Evaluation of the performance variation of porous air pads on discontinuous surfaces - Sanz, Claude; Morantz, Paul; Lunt, Alexander J. G.; Shore, Paul; Chérif, Ahmed; Schneider, Jürgen; Mainaud-Durand, Hélène; Steffens, Norbert (Elsevier, 2019)
A new high accuracy position measurement system has been developed. It measures the position of a 0.1 mm diameter copper-beryllium wire that informs alignment of energy beams in advanced particle accelerators. This new measurement system employs air pads to provide precision and friction free rotation of a sensor. To enable the measuring system to be positioned over the wire, a slot is required in the measuring device rotor. To optimise the design of this measuring system it was necessary to understand the performance of the air pads as they pass over the gaps (slots) in the rotor. This paper describes modelling and experiments that were performed to gain understanding of air pad performance when encountering such a surface gap. Particularly, an analytical model of the variation of load of a 20 mm × 40 mm porous air pad during the passing of a 1.5 mm wide slotted surface. Subsequent experimentation revealed that the general behaviour of the load variation had been captured effectively. The results of this analysis reveal that air pads of this size can reliably pass above an opening of this size with about 14% reduction in force. The results and the methodology presented in this paper can be used as an effective basis for future designs and studies
Keywords: Air bearing; Control; Accuracy